An investigative study into the Hazard Analysis Of Critical Control Point (HACCP) implementation in Small and Medium-Sized Food Manufacturing Enterprises (SMEs) / Muhammad Izzat Zulkifly...[et al.] - Mohd Zahari, Mohd Salehuddin; Jalis, Mohd Hairi; Othman, Zulhan (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2009)
This study investigates the Malaysian food SMEs’ main motive in implementing the system. It also assesses the effectiveness of the system’s implementation in the SMEs through the managements’ and employees’ commitment and the benefits of the system to the companies’ productivity. Sample populations were selected among the food SMEs that had implemented HACCP in the Klang Valley area. The face-to-face interview approach among the representative managers provided truly significant and in-depth information and it was found that the ‘customer requirement’ was the major motive of food SMEs in implementing HACCP, outnumbering the other motives identified. The managements’ and employees’ commitment after HACCP implementation were fairly satisfactory and HACCP offered numerous benefits for the companies’ productivity despite a few obstacles encountered during the implementation. Employees claimed that they were satisfied with the management’s commitment and were committed to their jobs after HACCP took place in their organization. Productivity experienced considerable improvement from HACCP implementation and the overall findings clearly indicate that HACCP is a good food safety system, and it is worthwhile for the other food SMEs toinvest in its implementation